Single-n versus multiple-n simulations of Alfvénic modes. (29th June 2018) - Vlad, G.; Briguglio, S.; Fogaccia, G.; Fusco, V.; Di Troia, C.; Giovannozzi, E.; Wang, X.; Zonca, F.
Abstract: The results of a set of simulations of Alfvén modes driven by an energetic particle population are presented, with the specific aim of comparing single- n and multiple- n simulations ( n being the toroidal mode number). The hybrid reduced O( ) MHD gyrokinetic code HMGC is used ( being the inverse aspect ratio of the torus, with a and R 0 the minor and major radius, respectively), retaining both fluid (wave–wave) and energetic particle nonlinearities. The code HMGC retains self-consistently, in the time evolution, the wave spatial structures as modified by the energetic particle (EP) term. Simulations with toroidal mode numbers have been considered. For the specific energetic particle drive considered, single- n simulations are either stable ( n   =  1), or weakly unstable ( ), or strongly unstable ( ), with modes exhibiting similar growth-rates, while n   =  4 the largest saturated amplitude. A variety of modes are observed (TAEs, upper and lower KTAEs, EPMs). Nevertheless, no appreciable global modification of the EP density profile is observed at saturation. On the contrary, a multi- n, fully nonlinear simulation exhibits an appreciable broadening of the EP radial density profile at saturation, thus demonstrating an enhanced radial transport w.r.t. the single- n simulations. Moreover, the sub-dominant modes are strongly modified by nonlinear coupling which results both from the MHD and from the EP terms.